2012
DOI: 10.1124/jpet.112.196949
|View full text |Cite
|
Sign up to set email alerts
|

Late Sodium Current Inhibition Alone with Ranolazine Is Sufficient to Reduce Ischemia- and Cardiac Glycoside-Induced Calcium Overload and Contractile Dysfunction Mediated by Reverse-Mode Sodium/Calcium Exchange

Abstract: Excessive reverse-mode (RM) sodium/calcium exchanger 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…VF results in global cardiac ischemia, and it is demonstrated that cardiac ischemia is associated with increases in the late Na + current and subsequent intracellular Na + overload. 9,12,17,18,20 Compensatory mechanisms are subsequently activated, including Na + -Ca 2+ exchanger reverse mode, 10,11 which can result in Ca 2+ overload in cardiomyocytes. This provides a potential substrate for various cardiac arrhythmias as demonstrated in several previous studies.…”
Section: + Current Blockade and Vf And Refibrillationmentioning
confidence: 99%
“…VF results in global cardiac ischemia, and it is demonstrated that cardiac ischemia is associated with increases in the late Na + current and subsequent intracellular Na + overload. 9,12,17,18,20 Compensatory mechanisms are subsequently activated, including Na + -Ca 2+ exchanger reverse mode, 10,11 which can result in Ca 2+ overload in cardiomyocytes. This provides a potential substrate for various cardiac arrhythmias as demonstrated in several previous studies.…”
Section: + Current Blockade and Vf And Refibrillationmentioning
confidence: 99%
“…RAN, an effective I Na.L inhibitor in therapeutic concentrations (< 10 mΜ), can obviously lower the density of (31). However, in this study, RAN decreased the hypoxia-increased reverse I NCX by inhibiting I Na.L .…”
Section: Discussionmentioning
confidence: 62%
“…Ca 2+ is the key regulator of the majority of functions in cardiac myocytes, including metabolism, electric activity, contractility as well as apoptosis [154,169,170,[209][210][211][212]. Elevated cytosolic calcium leads to Ca 2+ overload in sarcoplasmic reticulum resulting in contractile dysfunction and increased risk for arrhythmia [51,[213][214][215][216][217].…”
Section: The Plateau Sodium Current In Heart Diseasesmentioning
confidence: 99%
“…Role of I Na,L in arrhythmogenesis Acquired or inherited increase of INa,L is associated with enhanced risk for cardiac arrhythmia and inhibition of INa,L was demonstrated to prevent or abolish arrhythmic electric activity of the heart [1,3,5,6,41,57,123,214,215]. There are multiple mechanisms INa,L might lead to manifest arrhythmic activity.…”
Section: The Plateau Sodium Current In Heart Diseasesmentioning
confidence: 99%
See 1 more Smart Citation